An exploration of the role of traditional health practitioners dreams in the diagnosis and treatment of mental illness in Blouberg Municipality, Limpopo Province - Masola, Nare Judy (My University, 2023)
Dreams have always been intriguing phenomena confronting humankind over many years. They have been perceived differently across time and space, with different meanings attached to their manifestation. The general understanding and perception about dreams was that they emanate from some supernatural powers. Dreams have been some of the subjects of inquiry within the field of psychology. In this context, dreams are commonly perceived to originate from ‘within – intra’’ the dreamer. This study sought to explore the role that dreams play in the work of Traditional Health Practitioners (THPs) when diagnosing and managing mental illness. The study espoused a qualitative research approach and phenomenology design. Twenty-six THPs were selected through snowball and purposive sampling methods from five villages in Blouberg Municipality (Limpopo Province). Data were collected using in-depth semi-structured interviews and analysed through interpretive phenomenological Analysis (IPA). The following themes were extracted from the findings of the study: the THPs’ perception of dreams; the essence of dream for THPs; perceived sources of dreams; methods used to confirm the contents of dreams; and methods used to interpret symbolic dreams. Based on the above phenomenological accounts by the participants, an explanatory model on the use of dreams by THPs in the diagnosis and treatment of mental illnesses was developed. The explanatory model suggests that dreams are divided into four categories, namely: dreams as form of vision; dreams as a form of enlightenment; dreams as a form of awareness raising; and, dreams as a form of spiritual communication. The study made significant contribution through the development of an explanatory model to understand the role of dreams in the diagnosis and treatment of mental illness by Traditional Health Practitioners. The model presented a comprehensive process of dreams as a diagnostic and treatment tool in mental health care practice in the African context.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2023
Keywords: Dreams; Limpopo Province; Mental illness; Traditional Health Practitioners; Treatment; Healers; Mental illness -- Diagnosis; Dream interpretation